Anticancer action of naturally occurring emodin for the controlling of cervical cancer - Priyanka S. Lande; Vaibhav S. Adhao; Jaya P. Ambhore; Kiran P. Gaikwad; Chanchal S. Chandak; Leena P. Joge (Open Exploration Publishing Inc., 2023)
One of the major causes of death on the globe is cancer. The fourth most frequent malignancy in women worldwide is cervical cancer. Several cancer patients are remaining incurable due to the emergence of medication resistance, despite notable advances in cancer research over the previous few decades. The importance of natural sources as possible therapeutic candidates may be significant. Anthraquinones are one of the many chemical families of natural products, and they stand out for their wide range of structural variations, notable biological activity, and low toxicity. A natural substance called emodin, an anthraquinone derivative, is present in the roots and rhizomes of several plants. This substance has demonstrated antineoplastic, anti-inflammatory, antiangiogenic, and antiproliferative properties. It is also capable of preventing cancer spread and can reverse cancer cells' multidrug resistance. Emodin, a broad-spectrum inhibitor of cancer cells, have anticancer properties in many different types of biological pathways. These molecular mechanisms in cancer cells include the suppression of cell growth and proliferation, deterioration of the cell cycle arrest, the start of apoptosis, antimetastasis, and antiangiogenic impact. Therefore, the aim of the present review summarised the antiproliferative and anticarcinogenic qualities of cervical cancer of emodin.